2004
DOI: 10.1079/phn2003555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the choice of food composition table on nutrient estimates: a comparison between the British and American (Chilean) tables

Abstract: Objective:To determine the level of agreement between the American (Chilean) and British food composition tables in estimating intakes of macronutrients and antioxidants. Design, setting and subjects: Information based on a food-frequency questionnaire with emphasis on antioxidants was collected from 95 Chileans aged 24-28 years. Nutritional composition was analysed using the British table of food composition and the American table of food composition modified by Chilean food items. Mean differences and limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Nutrient databases (NDBs), required to calculate nutrient intakes from food consumption data, are important potential sources of random and systematic dietary measurement errors (Bingham, 1987;Cameron and van Staveren, 1988;Southgate, 1992, 2003;Nieman et al, 1992;Guilland et al, 1993;Lee et al, 1995;Garcia et al, 2003;Hakala et al, 2003;Kim et al, 2003;Vaask et al, 2004). These errors, which will be detailed in this paper, can affect individual and population means as well as the distribution of nutrient intakes, and subsequently distort diet-disease associations.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient databases (NDBs), required to calculate nutrient intakes from food consumption data, are important potential sources of random and systematic dietary measurement errors (Bingham, 1987;Cameron and van Staveren, 1988;Southgate, 1992, 2003;Nieman et al, 1992;Guilland et al, 1993;Lee et al, 1995;Garcia et al, 2003;Hakala et al, 2003;Kim et al, 2003;Vaask et al, 2004). These errors, which will be detailed in this paper, can affect individual and population means as well as the distribution of nutrient intakes, and subsequently distort diet-disease associations.…”
Section: Introductionmentioning
confidence: 99%
“…a diet rich in fresh vegetables and fruits, improves respiratory function in the general population (Kelly et al 2003, Butland et al 1999, 2000, Shaheen et al 2010. Epidemiological studies looking into the effect of balanced nutrition have shown that subjects on a diet rich in fruits, vegetables, fish and whole grains had much better respiratory parameters (Butland et al 2000, Shaheen et al 2010, Garcia et al 2004. However, most studies/reports focus on the effect of individual nutrients, their groups or nutritional patterns, and this may offer a limited chance for the interpretation of diet's effect on lung health (Garcia et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the analytical methodologies, the tables differ from one another in the list of foods and in the nutrients in the same food due to crop, variety, environmental factors, and food production and preparation among others [5,[7][8][9]. Due to these factors, the use of international tables in national studies on food consumption assessment must be done with caution [31].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has showed that different values were found between the American [5]. The incorrect description of foods and source of nutritional data, the use of unsuitable analytical methods with inadequate sampling, and variations due to genetic factors, regional disparities, food preparation and processing, and seasonal variation are factors that can influence the nutrient amounts listed in food composition tables [4][5][6][7][8]. It is important to check whether the data on food composition tables are constantly updated, considering the changes in food composition over time, improved analytical methods for particular nutrients, or the inclusion of information for new dietary components [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation